How do you solve x^2+3=0?

1 Answer
Jan 6, 2017

Put all the variables on one side of the equal sign, then solve from there.

Explanation:

You want to get all the variables over to one side, so subtract 3 over to the right side. You should then get x^2=-3.

You'd then square root both sides to get the simplified version of x.

sqrt(x^2)=sqrt(-3)

The square root of x^2 is simply x, but the sqrt(-3) is more complicated, as you can't get the square root of a negative number. You'd have to involve i, or the idea of an imaginary number.

(Right now, we have x=sqrt(-3)

Because i=sqrt(-1), we could multiply our 3 and i.
If sqrt(-3) = 3*sqrt(-1) = 3i, then x=3i.